2005
DOI: 10.1385/bter:107:1:061
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Selenium in Libyan Food Items Using Pseudocyclic Instrumental Neutron Activation Analysis

Abstract: Cyclic and pseudocyclic instrumental neutron activation analysis (INAA) has been used to determine the Se content of 40 Libyan food items. The selected samples include different varieties of local and imported foods such as wheat and barley products (bran and flours), rice, bread, almond, peanuts, vegetables as bean and peas, tea, coffee, sugar, and commonly used spices such as red and black paper, curry, cumin, mixture of spices, thyme, coriander, and fenugreek. Both conventional and anticoincidence gamma-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…al. (2005) has reported that daily intake of Se in Libyan population for all food ranged between 13 to 44 µg/day [18]. However, here in the current study, the data showed daily intake of Se from cereal consumption can be exposed 34 µg/day.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…al. (2005) has reported that daily intake of Se in Libyan population for all food ranged between 13 to 44 µg/day [18]. However, here in the current study, the data showed daily intake of Se from cereal consumption can be exposed 34 µg/day.…”
Section: Resultscontrasting
confidence: 69%
“…al. study [18] appearance that Libyan population DOI: 10.9790/5736-1005029195 www.iosrjournals.org 95 |Page has Se deficiency. From our study we can say more investigations should be done to have good view of Se situation in Libyan population.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that in the Libyan soil selenium concentration is somewhat lower than in other countries, especially in the Southern part of Libya where a number of cereal crops implementation projects are present. Because the soil is poor in selenium, the low level of selenium is reflected in Libyan foods [24]. Darnah farms contain the highest amount of selenium in this study.…”
Section: Resultsmentioning
confidence: 75%
“…The entire process repeats for a number of cycles [3,4]. In the case of sample with high dead time, a pseudo-cyclic NAA (PCNAA) technique was alternatively developed based on CNAA by adjusting the CNAA timing parameters [5][6][7][8], especially the waiting time between the repetitions of the irradiationdecay-counting cycles, which allowed to elapse in several minutes to days to reduce the dead time of spectrometer. Another alternative technique is a cumulative NAA, which was developed from irradiation and counting of a number of replicates of the same sample, the individual spectra are combined to generate a total spectrum [9,10].…”
Section: Introductionmentioning
confidence: 99%